Recent advances in the molecular beacon technology for live-cell single-molecule imaging (2020)
Nucleic acids, aside from being best known as the carrier of genetic information, are versatile biomaterials for constructing nanoscopic devices for biointerfacing, owing to their unique properties such as specific base-pairing and predictable structure. For live-cell analysis of native RNA transcripts, the most widely used nucleic acid-based nanodevice has been the molecular beacon (MB), a class of stem-loop forming probes that is activated to fluoresce upon hybridization with target RNA. Here, we overview efforts that have been made in developing MB-based bioassays for sensitive intracellular analysis, particularly at the single-molecule level. We also describe challenges that are currently limiting the widespread use of MBs and provide possible solutions. With continued refinement of MBs in terms of labeling specificity and detection accuracy, accompanied by new development in imaging platforms with unprecedented sensitivity, the application of MBs is envisioned to expand in various biological research fields.